Case Report: The Binocular Status of Two Mono-Vision Patients - Sévigny, Jacques (Canadian Journal of Optometry, 1982)
Two presbyopic patients were fitted with contact lenses, using the mono-vision technique. The results were evaluated considering the binocular status of the patients, fusion, stereopsis, distance and near acuity and subjective perception of vision.